Influencer-Driven Live Commerce and Repurchase Intentions: Evidence from Muslim Fashion on TikTok Shop - Winasis, Rafasya Syauqila; Septiarini, Dina Fitrisia (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study aims to analyze the influence of marketing strategies through TikTok Shop Live by influencers on consumer repurchase intention on Sattka Basic Hijab products. In the digital era, the use of live commerce has become an increasingly popular approach in building direct interactions with consumers, especially through the TikTok platform. This study uses a quantitative approach with a survey method on 192 respondents who have watched and/or purchased Sattka Basic Hijab products through TikTok Shop Live. The variables studied include influencer marketing, message appeals, brand image and product quality, Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS software. The results of the study show that influencer marketing, message appeals , brand image, and product quality have a significant effect on repurchase intention. These findings provide strategic implications for business actors in maximizing the role of influencers and compiling interesting content in live commerce to increase consumer loyalty.